Nitrogen and Sulfur Fertilization in Soybean: Impact on Seed Yield and Quality - L. H. Moro Rosso; W. D. Carciochi; S. L. Naeve; P. Kovács; S. N. Casteel; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2020)
Over time, plant breeding efforts for improving soybean [Glycine max(L.) Merr.] yield was prioritized and effects on seed nutritional quality were overlooked, decreasing protein concentration. This research aims to explore the effect of nitrogen (N) and sulfur (S) fertilization on soybean seed yield, seed protein and sulfur amino acids concentration. In 2018, ten field trials were conducted across the main US soybean producing region. The treatments were fertilization at 1) planting (NSP); during 2) vegetative growth (NSV); and 3) reproductive growth (NSR) and 4) unfertilized (Control). Nitrogen fertilization was applied at the rate of 40 lb/a utilizing urea ammonium nitrate (UAN), and S at 9 lb/a via ammonium sulfate (AMS). A meta-analysis was performed to consider small variations among experimental designs. A summary of the effect sizes did not show effects for seed yield. However, fertilization at planting (NSP) increased seed protein by 1% more than the control across all sites. Overall, sulfur amino acid concentration increased by 1.5% relative to the control, but the most consistent benefit came from fertilization during the reproductive growth (NSR), increasing sulfur amino acids by 1.9%. Although N and S fertilization did not affect seed yields, applying N and S in different stages of the crop growth can increase protein concentration and improve protein composition, providing the opportunity to open new US soybean markets.
Keywords: protein; amino acids; seed composition